COMMUNITY EMPOWERMENT IN THE USE OF CELERY PLANT (Apium graveolens L) AS AN ANTIHYPERTENSION IN PATIHAN VILLAGE, SIDOHARJO DISTRICT, SRAGEN. - Kurniawan Kurniawan; Satwika Budi Sawitri (Jurnal Abdimas Kesehatan (JAKes), 2023)
Hypertension is one of the most frequent cardiovascular diseases and is suffered by many people. Hypertension has now become a major problem for all of us, not only for Indonesia but also throughout the world, because hypertension is one of the triggers or risk factors for many other diseases such as diabetes. , heart disease, stroke and kidney failure, hypertension is now ranked third as a risk factor for death. In 2025, the increase in hypertension cases, especially in developing countries, is estimated at 80% from 639 million cases in 2000 or around 1.15 billion cases [1]). In pharmacognosy and phytotherapy, celery leaves are known to contain apigenin which can prevent the narrowing of blood vessels and can also relax artery muscles or relax blood vessels. This substance is able to regulate blood flow, allowing blood vessels to loosen or enlarge and reduce blood pressure. Based on this, it is necessary to carry out a community empowerment activity program in the use of celery plants to help overcome the problem of hypertension, which is implemented in the Community Service program under the PKM scheme with the partners being PC IAI Sragen and residents of Patihan Village, Sidoharjo District, Sragen. This PKM activity took place with five activities, namely: Checking participants' blood pressure before treatment and also using celery plants, initially carrying out a pre-test on participants before counseling, weighing and giving celery plants to be distributed to each participant so that they are able to carry out therapy. alone at home, conducting lectures and discussions about the use of traditional plants for hypertension, antihypertensive chemical medicines, and the use of celery plants for antihypertension, demonstrations on making herbal drinks from celery plants which are efficacious as antihypertensives and distributing drinks to participants, carrying out post-tests. The solution offered is an increase in the knowledge, attitudes and skills of PKM partners as shown by an increase in post-test scores after being compared with the pre-test scores. Apart from that, there was also an increase in the level of public health with a decrease in blood pressure, especially in participants who suffered from hypertension after being treated with celery leaves.